Improving Bottleneck Features For Vietnamese Large Vocabulary Continuous Speech Recognition System Using Deep Neural Networks / Quoc Bao Nguyen, Tat Thang Vu, Chi Mai Huong - Quoc Bao Nguyen
In this paper, the pre-training method based on denoising auto-encoder is investigated and proved to be good models for initializing bottleneck networks of Vietnamese speech recognition system that result in better recognition performance compared to base bottleneck features reported previously. The experiments are carried out on the dataset